1975
DOI: 10.1070/pu1975v018n08abeh004929
|View full text |Cite
|
Sign up to set email alerts
|

Dmitriĭ Nikolaevich Nasledov (obituary)

Abstract: The results of recent experimental and theoretical studies concerning the effects of plasma shape and current and pressure profiles on edge instabilities in DIII-D are presented. Magnetic oscillations with toroidal mode number n ≈ 2-9 and a fast growth time γ −1 = 20-150 µs are often observed prior to the first giant type I ELM in discharges with moderate squareness. High n ideal second ballooning stability access encourages edge instabilities by facilitating the buildup of the edge pressure gradient and boots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…For small undulator lengths we have found that the spectral bandwidth shrinks as 1/N, in agreement with the undulator radiation spectrum width [13]. In the highgain region the envelope reaches the well known bandwidth [3,5] Ak/k, = 2p, i.e.…”
supporting
confidence: 82%
“…For small undulator lengths we have found that the spectral bandwidth shrinks as 1/N, in agreement with the undulator radiation spectrum width [13]. In the highgain region the envelope reaches the well known bandwidth [3,5] Ak/k, = 2p, i.e.…”
supporting
confidence: 82%
“…and N w ≫ 1, major simplifications arise because fast oscillating terms in powers of exp[ik w z ′ ], which explicitly appear in Eq. (6) after substituting the trajectory [24], effectively average to zero after integration in dz ′ . To complete the resonance approximation, we further select frequencies such that…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Before the calculation, we will investigate a limiting case of the ®eld pattern in (46). The far-®eld pattern of synchrotron radiation from the undulator is approximately written as (Alferov et al, 1973(Alferov et al, , 1974Kincaid, 1977) ExY L 9 sinN%2xaN sin%2x…”
Section: Basic Theory Of Synchrotron Radiationmentioning
confidence: 99%